2007
DOI: 10.1016/j.febslet.2007.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylethanolamine stimulates chemotactic migration and cellular invasion in SK‐OV3 human ovarian cancer cells: Involvement of pertussis toxin‐sensitive G‐protein coupled receptor

Abstract: We investigated whether lysophosphatidylethanolamine (LPE) modulates cellular signaling in different cell types. SK-OV3 ovarian cancer cells and OVCAR-3 ovarian cancer cells were responsive to LPE. LPE-stimulated intracellular calcium concentration ([Ca 2+ ] i ) increase was inhibited by U-73122, suggesting that LPE stimulates calcium signaling via phospholipase C activation. Moreover, pertussis toxin (PTX) almost completely inhibited [Ca 2+ ] i increase by LPE, indicating the involvement of PTX-sensitive G-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 23 publications
2
79
0
Order By: Relevance
“…While higher expression of LPA-1 was reported in OVCAR-3 cells, LPA3 is the major receptor type in SKOV-3 cells (Park et al, 2007). In the present study, we showed that LPA2 expression is higher than other types of LPA receptor in CAOV-3 cells.…”
Section: Discussionsupporting
confidence: 55%
“…While higher expression of LPA-1 was reported in OVCAR-3 cells, LPA3 is the major receptor type in SKOV-3 cells (Park et al, 2007). In the present study, we showed that LPA2 expression is higher than other types of LPA receptor in CAOV-3 cells.…”
Section: Discussionsupporting
confidence: 55%
“…Although only a few papers have reported the physiological function of LPE to date, LPE might modulate several biological responses, possibly through G-protein-coupled receptor. 34 On the other hand, LPI is thought to be produced from phosphatidylinositol in activated platelets, 27 and its involvement in the migration of smooth muscle cells has been proposed. 35 Recently, a series of elegant studies have demonstrated that the state of cell activation and the autotaxin levels may determine the production of LPA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that mRNA of TRPV2 is expressed in prostate (18). TRPV2 function may be regulated by some lysophospholipids identified and known to have a range of physiologic and pathologic effects, including stimulation of cancer cell migration (19)(20)(21). However, the question remains as to how TRPV2 is involved in tumor development and progression both in vitro and in vivo to an extremely aggressive castration-resistant stage and whether it could be a real hallmark of poor prognosis in patients suffering from PCa.…”
Section: Introductionmentioning
confidence: 99%